Representações de gestores e profissionais sobre o trabalho da rede de enfrentamento ao tráfico de pessoas com fins de exploração sexual em Sergipe - Lisboa, Lucivânia de Oliveira (2015)
Human traffic has been taken in a huge proportion in the last few decades, driven forward by socio economic inequality including all the kinds of race/ ethnicity, becoming an important point of the happening called "Human Traffic". This genres approaching research, is focused on analyze the actions of the managers and professionals about the work of the `Rede de EnfrentamentoaoTrafico de Pessoas para fins de exploração Sexual de Sergipe´, pointing trend and challenges daily faced. It´s based on the historical- dialectic which tries to comprehend the human traffic to the sexual exploring beyond this phenomenalistic expression, showing the particular and universal aspects in addition to some specificities of the object. Were used different information sources like: bibliographies, documents, oral sources by the semi-structured interviews with women, managers and professionals of the executing agencies, promotion areas and accountable defense. The result points besides others issues, the fragility and lack of ability inside of the management in actions in the department area, lack of communication between different opinions, hierarchy of services , none knowledge of the legislation and studies about the occurrence.